Penerapan Keterampilan Memainkan Talempong Kreasi Di Sanggar Saandiko Bukittinggi - Khintar Rajmal Chair; Marzam Marzam; Tulus Handra Kadir (SENDRATASIK UNP, 2019)
This research was a descriptive study, using a qualitative method approach. The main instrument in this study was the researcher himself and assisted by supporting instruments such as stationery, cameras and tape recorders. Data collection techniques were carried out by official data, observation, interviews and documentation. The steps data analysis were data reduction, data presentation and conclusions. The results of the research showed that, in the practicing process of talempong creation at Saandiko Studio, the trainer was very good at providing the Implementation of Talempong Creation Playing Skills at Saandiko Studio. It also proved that the trainer succeeded in providing training to studio members by using several methods, namely by applying the lecture, demonstration and drill method, so the trainer's aim to develop the skills of the studio members produced excellent talent in playing talempong creation